A Fleeting Glory: Self-Serving Behavior Among Celebrated MBA CEOs. (July 2016) - Miller, Danny; Xu, Xiaowei
Recent studies have criticized MBA programs for their association with self-serving behavior, although there is little empirical research to establish the firm-level consequences of that relationship. We explored whether MBAs versus non-MBAs in a sample of celebrated CEOs of major U.S. companies—thus CEOs who have achieved and had opportunity to exploit their fame—were more apt than their counterparts to engage in self-serving behavior that benefits them but disadvantages their companies. We assessed this behavior via the pursuit of costly growth strategies, an inability to sustain performance, and the capacity to obtain superior private benefits in compensation. Our analysis of 444 star CEOs celebrated on the covers of major business publications confirmed that an MBA education either fosters or is related to such behavior among these executives.